Synthesis and Characterizations of a Collagen-Rich Biomembrane with Potential for Tissue-Guided Regeneration - Silva, Marcos J.; Gonçalves, Carolina P.; Galvão, Kleber M.; D’Alpino, Paulo H. P.; Nascimento, Fábio D. (European Journal of Dentistry, 2019)
Objectives In this study, a collagen-rich biomembrane obtained from porcine intestinal submucosa for application in guided bone regeneration was developed and characterized. Then, its biological and mechanical properties were compared with that of commercial products (GenDerm [Baumer], Lumina-Coat [Critéria], Surgitime PTFE [Bionnovation], and Surgidry Dental F [Technodry]).Materials and Methods The biomembrane was extracted from porcine intestinal submucosa. Scanning electron microscopy, spectroscopic dispersive energy, glycosaminoglycan quantification, and confocal microscopy by intrinsic fluorescence were used to evaluate the collagen structural patterns of the biomembrane. Mechanical tensile and deformation tests were also performed.Statistical Analysis  The results of the methods used for experimental membrane characterizations were compared with that obtained by the commercial membranes and statistically analyzed (significance of 5%).Results The collagen-rich biomembrane developed also exhibited a more organized, less porous collagen fibril network, with the presence of glycosaminoglycans. The experimental biomembrane exhibited mechanical properties, tensile strength, and deformation behavior with improved average stress/strain when compared with other commercial membranes tested. Benefits also include a structured, flexible, and bioresorbable characteristics scaffold.Conclusions The experimental collagen-rich membrane developed presents physical–chemical, molecular, and mechanical characteristics similar to or better than that of the commercial products tested, possibly allowing it to actively participating in the process of bone neoformation.
Keywords: extracellular matrix; porcine intestinal submucosa; guided bone regeneration